Y los sueños, sueños son… - González Sarmiento, Olga (2015)
This article explores the relationship between sleepand learning. Many of the studies in the field ofneuroscience have been exploring that relationship;who sleeps a sufficient number of suitable hoursfor their age, learns best and if it comes to a childnot only learns best, but grows. Opportunities forlearning are given daily, so the importance of theissue. And dreams are dreams... it has discoveredfrom the field of neuroscience, they provideinteresting answers about sleep and learning.